2015
DOI: 10.1186/s13041-015-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

TMEM106B, a frontotemporal lobar dementia (FTLD) modifier, associates with FTD-3-linked CHMP2B, a complex of ESCRT-III

Abstract: BackgroundTransmembrane protein 106B (TMEM106B) has been identified as a risk factor for frontotemporal lobar degeneration, which is the second most common form of progressive dementia in people under 65 years of age. Mutations in charged multivesicular body protein 2B (CHMP2B), which is involved in endosomal protein trafficking, have been found in chromosome 3-linked frontotemporal dementia. Despite the number of studies on both CHMP2B and TMEM106B in the endolysosomal pathway, little is known about the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
(61 reference statements)
0
36
0
Order By: Relevance
“…These protein interactions together with TMEM106B’s endolysosomal localization would imply that the TMEM106B cytoplasmic domain possibly participates in the delivery of endocytic cargos to the lysosome. In agreement with this hypothesis, Jun and colleagues reported that TMEM106B also directly binds to CHMP2B [35], known to be a member of the endosomal sorting complexes required for transport III (ESCRT-III) complex that regulates endolysosomal protein trafficking and autophagic structure formation [27, 28]. One additional report identified the C-terminus of microtubule-associated protein 6 (Map6) to also directly bind the N-terminus of Tmem106b by utilizing mass spectrometry analysis of rat brain Tmem106b immunoprecipitation samples [66].…”
Section: Tmem106b Binding Partnersmentioning
confidence: 61%
See 3 more Smart Citations
“…These protein interactions together with TMEM106B’s endolysosomal localization would imply that the TMEM106B cytoplasmic domain possibly participates in the delivery of endocytic cargos to the lysosome. In agreement with this hypothesis, Jun and colleagues reported that TMEM106B also directly binds to CHMP2B [35], known to be a member of the endosomal sorting complexes required for transport III (ESCRT-III) complex that regulates endolysosomal protein trafficking and autophagic structure formation [27, 28]. One additional report identified the C-terminus of microtubule-associated protein 6 (Map6) to also directly bind the N-terminus of Tmem106b by utilizing mass spectrometry analysis of rat brain Tmem106b immunoprecipitation samples [66].…”
Section: Tmem106b Binding Partnersmentioning
confidence: 61%
“…Nonetheless, one feature found in patients with disease-causing CHMP2B mutations is the presence of large vacuolar structures in the brain that label positive for endosomal proteins, suggesting an endosomal-related disease mechanism [31]. Interestingly, Jun and colleagues found endogenous Tmem106b to partially co-localize to both wild-type CHMP2B- and mutant CHMP2B-positive structures in mouse neurons [35], further highlighting a potential role for TMEM106B in the endolysosomal pathway. Moreover, this study showed that T185 TMEM106B more readily binds to CHMP2B than S185 TMEM106B, and that T185 TMEM106B-CHMP2B binding is enhanced with the mutant form of CHMP2B [35].…”
Section: Linking Tmem106b To Other Ftld Disease Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-immunoprecipitation and western blotting were performed as previously described (Jun et al, 2015; Kim et al, 2014). Briefly, HEK293T cells were transfected with a 3XFLAG-PKMζ (interaction between PKMζ and importin) or 3XFLAG-CBP and pCMV-PKMζ (interaction between PKMζ and CBP) expression plasmid.…”
Section: Methodsmentioning
confidence: 99%